Molecular and functional characterization of porcine Siglec-3/CD33 and analysis of its expression in blood and tissues. Issue 2 (August 2015) - Álvarez, B.; Escalona, Z.; Uenishi, H.; Toki, D.; Revilla, C.; Yuste, M.; del Moral, M. Gómez; Alonso, F.; Ezquerra, A.; Domínguez, J.
Highlights Cell lines expressing the porcine homologue of Siglec-3/CD33 have been generated. Monoclonal antibodies to porcine Siglec-3 have been developed. Porcine Siglec-3 is mainly expressed on myeloid cells and their precursors.